Theological Postcards from the Ecological Edge - Pearson, Clive R. (Journal for the study of religion, nature and culture, 1998)
One of the everyday myths of pakeha in Aotearoa-New Zealand is that we live in a ‘clean, green and beautiful land’. Tucked away at the ends of the earth we inhabit a slice of theological geography that we regularly tell ourselves both in cartoon form and everyday conversation is ‘Godzone’. The arrivals’ lounge at our international airports, and the sea cruises advertised every Saturday morning in the Sydney Morning Herald, testify to the popular appeal of majestic mountains, deep fjords, glaciers on which you can land a small plane, gorges into which you might bungy-plummet, spouting geysers, smoking volca-noes, porridge-like pools of boiling mud, the occasional earthquake ( . . . is Wellington still with us?), fields of green, seldom seen flightless birds, and that great favourite, the performing sheep at the Rotorua Agrodome: ‘Welcome to our world’. Cameras/videos at the ready . . . start shooting . . . picture perfect.